1982
DOI: 10.1017/s0022112082002286
|View full text |Cite
|
Sign up to set email alerts
|

Corrections of hot-wire anemometer measurements near walls

Abstract: Applications of hot-wire anemometers to velocity rneaaurements near walls can result in erroneous velocity data owing to additional heat losses to the wall. It is difficult to account for these errors if calibration data are used that were obtained in calibration test rigs without walls. This has been recognized in many studies in which hot-wires were applied to measurements in wall boundary-layer flows and different suggestions for corrections have been given. The present paper summarizes these suggested corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 8 publications
2
34
0
1
Order By: Relevance
“…The overheat ratio was set at 1)3 so as to minimize the heat conduction loss to the Plexiglas wall (Bhatia et al 1982;Turan & Azad 1987). All hot-wire calibrations, mean-flow measurements, free-stream turbulence levels, r.m.s.…”
Section: Hot-wire Anemometrymentioning
confidence: 99%
“…The overheat ratio was set at 1)3 so as to minimize the heat conduction loss to the Plexiglas wall (Bhatia et al 1982;Turan & Azad 1987). All hot-wire calibrations, mean-flow measurements, free-stream turbulence levels, r.m.s.…”
Section: Hot-wire Anemometrymentioning
confidence: 99%
“…In the innermost region of the profile, y+ = 8 through y+ = 35, the characteristic deviation from the theoretical lines, which has been noted by many Ligrani and Bradshaw (1987), also appears in the present measurements. Due to the very thin plastic laminate of the surface of the flat plate, this plate may be classified as a non-conducting wall, and since the innermost points of the present measurements are located as far from the wall as at y+ =8, no wall corrections are needed accoding to Bhatia et al (1982). The directional sensitivity of the silicon sensors is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After Wills [2], Polyakov and Shindin [4] revisited the hot-wire peculiarities near walls of different thermal conductivities (steel, copper and textolite). They showed that the deviation in hot-wire readings is mainly af- [4] was then followed by a numerical study carried out by Bhatia et al [5] for walls representing ideally conducting and nonconducting (adiabatic) materials. Their corrections were found to be independent of the wall friction velocity, u s , when measured data are plotted as DU þ ¼ f ðy þ Þ, and corrections for conducting materials are needed close to the wall, i.e., y þ 6 2:5.…”
Section: Summary Of Existing Knowledgementioning
confidence: 99%